Informe de pasantía en el área de mercadeo internacional de la empresa LÍDER & CO S.A.S. (2022)
The actual report shows the activities that were made to Lider & CO S.A.S company, which correspond to three specific duties. Firstly, the searching of possible indigo and drill fabric suppliers, where Yamei Textile was the one identified as the Chinese company that can supply the demand for raw matterials required by Lider. Secondly, the obtained results are found from the participation in the international offer quote form specifically in the one directed to Provefarma Ecuador. Furthermore, the achieved scope after the tracking of Coca-Cola Femsa orders, one of the most representative customer for Lider in a matter of sales, has managed to be satisfying and complete. Finally, with the achieved activities, the marketing area received the expected support from the practitioner in its operative activities, leaving satisfaction both in the company and in the practitioner